Estrategias metodológicas y su incidencia en el proceso de enseñanza-aprendizaje de los estudiantes de bachillerato de la especialidad de Electricidad de la Unidad Educativa Siete de Octubre de la Ciudad de Quevedo. Periodo lectivo 2016-2017. - Vique Salazar, Guillermo Ismael (2016)
The Siete de Octubre Educational Unit, an institution at the service of the Quevede community, motivated by the promotion of professionals in the technical areas of Electricity, Automotive Mechanics and Industrial Mechanics, has allowed the productive improvement based on the requirements of the competent society, the difficulties Which addresses the present research responds to the need to improve the teaching-learning process of high school students of the specialty of electricity of the Educational Unit Siete de Octubre. The main objective of this research is to evaluate the impact of the methodological strategies in the teaching-learning process of the students, allowing to investigate the competences applied in the teaching faculty in order to enhance the weaknesses that appear in the different academic scenarios, One of the requirements that must be established at the level of education is the continuous improvement through the permanent evaluation in order to measure significant changes in the construction of knowledge in students, it is sought to investigate how the inappropriate use of educational activities Negatively in the process of meaningful learning. The impact of the Methodological Strategies in the teaching-learning process is evaluated in order to improve the weaknesses generated in this process, to strengthen the construction of meaningful learning and its continuous improvement.